New country records for species of Boraginaceae and Lamiaceae in the Horn of Africa hotspot - Thulin, Mats; Larsson, Anders (Phytotaxa, 2021)
Cystostemon heliocharis (Boraginaceae), previously known from Yemen and Somalia, is reported from Ethiopia, and a photograph of the species is provided. Trichodesma stocksii (Boraginaceae), previously known from Pakistan, Iran, and Oman, is reported from Yemen, and a drawing based on a Yemeni collection is provided. Clerodendrum hildebrandtii (Lamiaceae), previously known from Somalia, Kenya, Tanzania, and Mozambique, is reported from Ethiopia, based on a photographic record. Distribution maps showing the total distribution of these three species are presented.